Serum long non coding RNA MALAT-1 protected by exosomes is up-regulated and promotes cell proliferation and migration in non-small cell lung cancer - Zhang, Rui; Xia, Yuhong; Wang, Zhixin; Zheng, Jie; Chen, Yafei; Li, Xiaoli; Wang, Yu; Ming, Huaikun (Biochemical and biophysical research communications, 2017)
Circulating lncRNAs have been defined as a novel biomarker for non-small cell lung cancer (NSCLC), MALAT-1 was first identified lncRNA that was related to lung cancer metastasis. However, the relationship between exosomal lncRNAs and the diagnosis and prognosis of NSCLC was poorly understood. The aim of this study is to evaluate the clinical significance of serum exosomal MALAT-1 as a biomarker in the metastasis of NSCLC. In this study, we firstly isolated the exosomes from healthy subjects and NSCLC patients. Then we measured the expression levels of MALAT-1 contained in exosomes, and found that exosomal MALAT-1 was highly expressed in NSCLC patients, more importantly, the levels of exosomal MALAT-1 were positively associated with tumor stage and lymphatic metastasis. In addition, we decreased MALAT-1 expression by short hairpin RNA and conducted a series of assays including MTT, cell cycle, colony formation, wound-healing scratch and Annexin/V PI by flow cytometry in human lung cancer cell lines. These in vitro studies demonstrated that serum exosome-derived long noncoding RNA MALAT-1 promoted the tumor growth and migration, and prevented tumor cells from apoptosis in lung cancer cell lines. Taken together, this study shed a light on utilizing MALAT-1 in exosomes as a non-invasive serum-based tumor biomarker for diagnosis and prognosis of NSCLC. •serum MALAT-1 contained in exosomes is upregulated in NSCLC patients.•Exosomal MALAT-1 was positively associated with TNM stage and lymphatic node metastasis.•MALAT-1 knockdown inhibited cell proliferation, colony formation and cell migration.•MALAT-1 knockdown induced cell cycle arrest and cell apoptosis.